2018
DOI: 10.1111/jace.15999
|View full text |Cite
|
Sign up to set email alerts
|

Spark plasma sintering microscopic mechanisms of metallic systems: Experiments and simulations

Abstract: The microscopic densification mechanisms of metallic systems (TiAl, Ag-Zn) by spark plasma sintering (SPS) have been studied by simulations and experiments. Finite element simulations showed that, despite very high current densities at the necks between metallic powder particles (≈5 × 10 4 A/cm 2 ), only very limited Joule overheating can be expected at these locations (<1°C), because of very fast heat diffusion. The microscopic plasticity mechanisms under these high electric currents have been studied by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…The breakdown of surface oxide films is more likely happening due to plastic deformation and reduction at higher temperatures [33], possibly in conjunction with the presence of carbon [34]. A multitude of experimental observations [35,36], analytical estimates, and finite element simulations [37][38][39][40] even come to the conclusion that with less than 1 K no relevant temperature difference between particle-particle contacts and the centre of the particles exists.…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown of surface oxide films is more likely happening due to plastic deformation and reduction at higher temperatures [33], possibly in conjunction with the presence of carbon [34]. A multitude of experimental observations [35,36], analytical estimates, and finite element simulations [37][38][39][40] even come to the conclusion that with less than 1 K no relevant temperature difference between particle-particle contacts and the centre of the particles exists.…”
Section: Introductionmentioning
confidence: 99%
“…In the early works, very elevated local current densities, leading to local high overheating at the contacts (up to 10,000 °C), were computationally calculated [8,11]. The main limitation of these simulations is that they did not consider heat conduction within the particles, which was later shown to play a major role [12][13][14][15][16]. Even though more recent simulations predict local current densities as high as ≈ 5 × 10 4 A/cm 2 at the contacts between particles [15][16][17], it has been shown that, for regularsize powder particles (≈ 100 µm), the temperature homogenization by heat conduction takes only milliseconds, which was not compatible with stabilization of "hot spots" at the particle contacts [15,16].…”
Section: Microscopic Densification Mechanismsmentioning
confidence: 99%
“…The main limitation of these simulations is that they did not consider heat conduction within the particles, which was later shown to play a major role [12][13][14][15][16]. Even though more recent simulations predict local current densities as high as ≈ 5 × 10 4 A/cm 2 at the contacts between particles [15][16][17], it has been shown that, for regularsize powder particles (≈ 100 µm), the temperature homogenization by heat conduction takes only milliseconds, which was not compatible with stabilization of "hot spots" at the particle contacts [15,16]. Few experimental works with FeAl [18] and metallic glasses [19] concluded local overheating, but clear and direct evidence could not be provided.…”
Section: Microscopic Densification Mechanismsmentioning
confidence: 99%
“…This technology integrates plasma activation, hot pressing and resistance heating, and directly connects the high-frequency pulse current between the pressurized powder particles. This technology depends upon heat from the plasma produced by spark discharge, which has the advantages of fast heating and cooling speeds, a low sintering temperature, short sintering time, fine and uniform grain size, controllable microstructure, and so on [9,10,11]. Therefore, advantages of SPS technology can be used to try to solve the defects of traditional porous titanium.…”
Section: Introductionmentioning
confidence: 99%